2022
DOI: 10.1371/journal.pone.0277315
|View full text |Cite
|
Sign up to set email alerts
|

Cisnormativity as a structural barrier to STI testing for trans masculine, two-spirit, and non-binary people who are gay, bisexual, or have sex with men

Abstract: Trans masculine, two-spirit, and non-binary people who are gay, bisexual or otherwise have sex with men (TGBM) are under-tested for sexually transmitted infections (STI) and may face complex, intersectional barriers that prevent them from accessing STI testing. As part of a study on gay, bisexual and other men who have sex with men’s (GBM) experiences of current STI testing systems in Ontario, Canada, this paper reports on the findings from TGBM participants’ experiences with in-person STI testing in a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Although Taylor noted that HCPs are trying to be more inclusive of queer and trans individuals, they required the physical support of friends when accessing in-person care. Participants also emphasized that barriers to healthcare persist in other forms, such as a failure to update personal documents to refect patients' current gender identity [73]. Casey described similar challenges seeking care, adding that misgendering and bureaucratic factors signifcantly impact the quality of care they had received in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Although Taylor noted that HCPs are trying to be more inclusive of queer and trans individuals, they required the physical support of friends when accessing in-person care. Participants also emphasized that barriers to healthcare persist in other forms, such as a failure to update personal documents to refect patients' current gender identity [73]. Casey described similar challenges seeking care, adding that misgendering and bureaucratic factors signifcantly impact the quality of care they had received in the past.…”
Section: Discussionmentioning
confidence: 99%
“…A discourse based on the assumption that cis-gender is the norm and privileges this over any other form of gender identity (Stewart et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…There is consensus within the literature that Western perinatal healthcare systems are built upon culturally and socially constructed cis-normative, heteronormative, feminine, gender binary foundations (Charter et al, 2018;Duckett & Ruud, 2019;Falck et al, 2021;García-Acosta et al, 2020;Jackson et al, 2022;MacDonald et al, 2016;McCann et al, 2021;Richardson et al, 2019;Wolfe-Roubatis & Spatz, 2015). While cis-gender is a term used when someone identifies with their gender assigned at birth, cis-normative is the assumption or belief that being cis-gender is normal and is therefore privileged over all other expressions of gender (Stewart et al, 2022). Ferri et al (2020) identify that this highly gendered assumption causes access barriers to perinatal healthcare.…”
Section: The Foundations Of Western Perinatal Healthcare Systemsmentioning
confidence: 99%
“…According to Stewart et al, 2022, the trans gay and bisexual male population faces unique structural and individual challenges when accessing health care compared to the cisgender population. Spaces segregated by gender, lack of competence of the care provider and barriers in the legal documentation that often does not represent the correct gender identity stand out.…”
Section: Gender Transition Phasementioning
confidence: 99%
“…In the study carried out by Gahagan and Malaret (2018), health professionals also identified concerns regarding legal documentation, noting that many trans users do not have their gender identity represented in legal identification documents. This incongruity often leads to poor evaluation of these people's sexual risk behaviors (Stewart et al, 2022).…”
Section: Gender Transition Phasementioning
confidence: 99%